The poetic rhetorical evidence in the book (Anwar al-Tahali on what was included in the poem of al-Halli) by Abu Abdullah bin Abi al-Qasim (787 AH): Study and Analysis - ALkhresheh, Ahmad Ghaleb (Journal of Humanities & Social Sciences, 2021)
This study investigates and analyzes the rhetorical and poetic evidence in Anwar al-Tahali as contained in the poem of al-Halli by Abu Abdullah ibn Abi al-Qasim (787 AH), a prominent figure in the Maghreb region. The study focuses on two areas: the way the author followed in introducing the rhetorical aspects through combining between the originality of the early rhetoricians and their attention to application and analysis on one hand, and the philosophy of later scholars and their focus on limitations and definitions on the other hand. The second area is that Abi al-Qasim attached a great attention to the poetic rhetorical evidence in his book through a clear approach based on analysis, explanation, examples. Preliminarily, the study introduces Anwar al-Tahali along with two areas. The first area includes the poetic rhetorical evidence of Ibn Abi al-Qasim and his position in relation to imitation and renovation, while the other area deals with the methodology of that position. The study, therefore, adheres to the descriptive – analytical approach. It concludes that Ibn Abi al-Qasim was able to break away from the stereotypical pattern that prevailed in the poetic rhetorical evidence after Abdul Qaher al-Jarjani. The study highlights the importance of studying the rhetorical evidence in the heritage of the ancients in general, and the later ones in particular, because this heritage contains a huge amount of evidence that we may not find in other sources.